pHLIP ICG for delineation of tumors and blood flow during fluorescence-guided surgery - Crawford, Troy (Sci Rep, 2020)
Fluorescence imaging has seen enduring use in blood flow visualization and is now finding a new range of applications in image-guided surgery. In this paper, we report a translational study of a new fluorescent agent for use in surgery, pHLIP ICG, where ICG (indocyanine green) is a surgical fluorescent dye used widely for imaging blood flow. We studied pHLIP ICG interaction with the cell membrane lipid bilayer, the pharmacology and toxicology in vitro and in vivo (mice and dogs), and the biodistribution and clearance of pHLIP ICG in mice. The pHLIP ICG tumor targeting and imaging efficacy studies were carried out in several murine and human mouse tumor models. Blood vessels were imaged in mice and pigs. Clinical Stryker imaging instruments for endoscopy and open surgery were used in the study. Intravenously administered pHLIP ICG exhibits a multi-hour circulation half-life, offering protracted delineation of vasculature. As it clears from the blood, pHLIP ICG targets tumors and tumor stroma, marking them for surgical removal. pHLIP ICG is non-toxic, marks blood flow for hours after injection, and effectively delineates tumors for improved resection on the day after administration.